Syntactic Inversion Use among EFL University Students in Academic Essay Writing (مجلة الواحات للبحوث والدراسات, 2026)
This study investigates the use of syntactic inversion in academic essays written by English as Foreign Language (EFL) university students. Combining both quantitative (corpus of 60 essays) and qualitative data tools (interview with eight students), findings reveal that despite its occurrence in their writings, students report their unawareness and less reliance on syntactic inversion. Additionally, noun phrase inversion is the most frequently used type followed by verb and adjective phrase inversions, while adverb and prepositional phrase inversions are less common.  Moreover, students perceive inversion use positively as it adds more clarity, formality, and variety to their writing.  Students also allude to some drawbacks that disrupt the overall flow, clarity, and cohesion of the essay when used inappropriately. They, therefore, suggest explicit instruction, guided practice, sufficient time for practice, and awareness of inversion drawbacks as key measures to improve the effective use of inversion in academic writing.